A Study on Iot-Enabled Smart Glasses for Visually Impaired - T, Hasna; Boopathi, P.; S, AnuKeerthana; Das, Athul K; kumar, Gulshan; S, Fathima (Journal of Neonatal Surgery, 2025)
IoT-enabled smart glasses for visually impaired individuals aim to provide real-time assistance by detecting obstacles and offering navigational support. This paper presents a novel approach to developing smart glasses integrated with IoT technologies, incorporating ultrasonic sensors, GPS, and NodeMCU ESP8266 to enhance the mobility and safety of visually impaired users. The system uses ultrasonic sensors to detect obstacles and provides feedback through a buzzer. A GPS module transmits real-time location data, including latitude and longitude, to the Esskay Live online platform. The proposed system aims to reduce mobility challenges and provide an affordable, user-friendly solution. The effectiveness of the system is evaluated through a prototype, demonstrating its potential to improve navigation for visually impaired individuals.